Key determinants of women's entrepreneurial intention and behavior: The role of business opportunity recognition and need for achievement - Houda Bouarir; Asmae Diani; Omar Boubker; Jaouad Rharzouz (Administrative Sciences, 2023)
The focus of this study is to investigate the major factors influencing entrepreneurial intent and behavior, by addressing the role of entrepreneurial education, business opportunity recognition, and the need for achievement. The research data were collected online using a self-administered questionnaire among 148 Moroccan women having completed an entrepreneurship training program. The data analysis using a PLS-SEM provided evidence of the positive impact of entrepreneurial education on entrepreneurial self-efficacy and PBC. Likewise, the findings supported the direct impact of subjective norms and entrepreneurial self-efficacy on entrepreneurial attitude. Furthermore, entrepreneurial attitude, business opportunity recognition, and the need for achievement were identified as predictors of entrepreneurial intent, leading to enhanced entrepreneurial behavior. These results highlight a number of useful practical recommendations for public policy-makers on how to stimulate and encourage entrepreneurship initiatives among women.
Keywords: 350; entrepreneurial education; entrepreneurship; Morocco; need for achievement; opportunity recognition; self-efficacy